Bear bile powder ameliorates type 2 diabetes via modulation of metabolic profiles, gut microbiota, and metabolites - Chen, Xing-Ling; Cai, Ke; Zhang, Wen; Su, Shu-Lan; Zhao, Li-Hui; Qiu, Li-Ping; Duan, Jin-Ao (Frontiers in Pharmacology, 2023)
Bear bile powder (BBP) is widely used in clinic and has hypoglycemic effect, but its mechanism is not clear. In this study, type 2 diabetes mellitus (T2DM) rats induced by high-sugar and high-fat diet combined with streptozotocin were given BBP, and biochemical indexes, pathological sections, metabonomics, intestinal microbiota (IM) and short-chain fatty acids (SCFAs) were determined. The results showed that BBP could reduce blood glucose, relieve inflammation, insulin resistance and lipid metabolism disorder, and alleviate tissue damage of liver, spleen, kidney and pancreas in T2DM rats. It is worth noting that BBP can reverse the changes of blood and urine metabolites in T2DM rats, which are mainly related to tryptophan metabolism, pentose and glucuronate interconversions, starch and sucrose metabolism and glycerophospholipid metabolism. In addition, BBP restored IM disorder in T2DM rats, decreased the abundance of Allobaculum, Blautia, Dubosiella and Anaerostipes, enriched the abundance of Lactobacillus, Romboutsia, UCG-005 and norank_f__Eggerthellaceae, and increased the concentration of SCFAs in intestinal contents. These findings suggest that BBP may improve T2DM by regulating multiple metabolic pathways, IM composition and SCFAs levels.